Desarrollo de un plan metodológico para la operación de una máquina universal de ensayos modelo Shimadzu AGS-X según las normas ASTM (2019)
The objective of this project is the development of a methodological plan for the operation of a Shimadzu AGS-X universal testing machine, according to ASTM standards, taking into account that this equipment is currently new and is not 100% utilized. This research seeks to characterize the universal machine allowing to know the types of tests that can be performed on it, types of specimens that can be used and materials that can be tested on it depending on their capacity. For the development of this proposal, two types of ceramic, plastic and metallic materials were selected in order to perform 3-point tension, compression and bending tests. Once the specimens were manufactured, the tests were performed on the universal machine to know specific mechanical properties of each material tested. After obtaining the results, an analysis was performed for each trial, identifying percentages of error and behaviors according to ASTM standards. Finally, the costs of each trial were evaluated.